Bone Regeneration: A Novel Bone Substitute with High Bioactivity, Strength, and Porosity for Repairing Large and Load‐Bearing Bone Defects (Adv. Healthcare Mater. 8/2019). Issue 8 (25th April 2019) - Li, Jiao Jiao; Dunstan, Colin R.; Entezari, Ali; Li, Qing; Steck, Roland; Saifzadeh, Siamak; Sadeghpour, Ameneh; Field, John R.; Akey, Austin; Vielreicher, Martin; Friedrich, Oliver; Roohani‐Esfahani, Seyed‐Iman; et al.
Abstract : In article number1801298, Hala Zreiqat and co‐workers showcase a Sr‐HT‐Gahnite bone substitute implanted in a sheep tibial segmental defect for one year. Focused ion beam scanning electron microscopy (FIB‐SEM) cross‐section of the implant‐bone interface shows nanoscale detail of the scaffold (top) and loose connective tissue (bottom), between which is a disrupted zone of ceramic degradation and tissue infiltration.